Acupuncture for pediatric chronic pain: a systematic review - Bissoto, João Roberto; Silva Júnior, José Udevanier Rebouças da; Alvares, Gabrielle Pignoli [UNESP]; Santos, Flávia H.; Len, Claudio Arnaldo (Elsevier, 2024)
Objectives: To survey, analyze and discuss the scientific evidence supporting the use of acupuncture and related techniques in the management of chronic pain in the pediatric population. Sources: A survey of databases (MEDLINE, Scopus and Scielo) was carried out with search strategies, following the PRISMA statement, without limits on publication dates and languages. Clinical studies (clinical trials, single-arm, and case series) were accepted for review if they included participants aged up to 22 years. Study quality was assessed by MMAT, and the randomized clinical trial was analyzed under the STRICTA criteria. Summary of the findings: 2369 articles were retrieved. After excluding repetitions, 1335 underwent the initial selection. Only 16 articles were selected for full reading, of which 5 were included in the review, being two case series, two single-arm studies, and one randomized clinical trial. The articles were considered of good quality by the adopted criteria. Conclusion: The analyzed studies showed important clinical results such as the reduction of pain intensity, and improvement in school attendance and social life. However, there are many limitations in study design and sample size. Therefore, there is weak evidence to support the use of acupuncture in the context of pediatric chronic pain, but the positive results reinforce the need for further investigation of the topic with the conduct of larger and well-designed studies, to obtain more data and greater scientific conviction of the findings.
Keywords: Acupuncture; Adolescent; Child; Chronic pain; Pain management